Specializations of the mandibular anatomy and dentition of Segnosaurus galbinensis (Theropoda: Therizinosauria) - Lindsay E. Zanno; Khishigjav Tsogtbaatar; Tsogtbaatar Chinzorig; Terry A. Gates (PeerJ, 2016)
Definitive therizinosaurid cranial materials are exceptionally rare, represented solely by an isolated braincase and tooth in the North American taxon Nothronychus mckinleyi, the remarkably complete skull of the Asian taxon Erlikosaurus andrewsi, and the lower hemimandibles of Segnosaurus galbinensis. To date, comprehensive descriptions of the former taxa are published; however, the mandibular materials of S. galbinensis have remained largely understudied since their initial description in 1979. Here we provide a comprehensive description of the well-preserved hemimandibles and dentition of S. galbinensis (MPC-D 100/80), from the Upper Cretaceous Bayanshiree Formation, Gobi Desert, Mongolia. The subrectangular and ventrally displaced caudal hemimandible, extreme ventral deflection of the rostral dentary, and edentulism of the caudal dentary of S. galbinensis are currently apomorphic among therizinosaurians. Unique, unreported dental traits including lingually folded mesial carinae, development of a denticulated triangular facet on the distal carinae near the cervix, and extracarinal accessory denticles, suggest a highly specialized feeding strategy in S. galbinensis. The presence of triple carinae on the distalmost lateral tooth crowns is also unique, although may represent an abnormality. Contrasted with the simplistic dentition of the contemporaneous therizinosaurid E. andrewsi, the dentition of S. galbinensis is indicative of niche partitioning in food acquisition, processing, or resources among known therizinosaurids inhabiting Asian ecosystems in the Late Cretaceous. Although not quantitatively correlated with diet, this suite of specializations is otherwise unique among theropod dinosaurs and supports derived inferences of facultative or obligate herbivory in therizinosaurids, ultimately adding novel information to our understanding of ecomorphology in theropods.